Nevelődés, beavatás, mese: Tamási Áron Ábel a rengetegben című regényének műfaji elemzése - Baranyai, Norbert (Studia Litteraria, 2019)
This paper attempts to reinterpret Áron Tamási’s most significant novel, Ábel a rengetegben (Abel in the Forest). The interpretation approaches the text from genre reading, according to which the analysis understands the text’s exemplary meanings based upon the genres of Bildungsroman, tale and initiation story. The paper sets out to demonstrate that the text’s poetic achievement can be best understood as the polyphony of meanings in themes, motifs as well as in linguistics–rhetoric, regardless its understanding as wish fulfilment in tales, or as successful educational process filled with tests, or as the parable of minority fate.